Bahtsul Masā'il as a Model of Collective Ijtihad in Traditional Islam: An Epistemological and Methodological Analysis of the Mudzakarah Ma'al-Ikhwan Forum - Imam Syarbini; Asmawi Asmawi; Kojin Kojin (Al-Qalam Institue, 2025)
This study aims to examine Bahtsul Masā'il as a model of traditional Islamic collective ijtihād by analyzing the epistemological foundations and methodological practices of the Ma'al-Ikhwan Mudzakarah Forum at Salafiyah-Syafi'iyah Islamic Boarding School, Sukorejo, East Java, Indonesia. The research employed a qualitative case study design involving participant observation, semi-structured interviews with kiai, forum leaders, musahhih, teachers, and senior students, as well as document analysis of forum proceedings and legal decisions. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing, while data credibility was ensured through source triangulation, method triangulation, and member checking. The findings reveal that the forum develops an integrative model of collective ijtihād by combining classical Islamic legal sources (kutub al-turāth), uṣūl al-fiqh, qawā'id fiqhiyyah, maqāṣid al-sharī'ah, and contextual analysis within a structured deliberative process. The study also demonstrates that methodological contestation functions as a constructive mechanism for strengthening legal reasoning rather than generating institutional conflict. It concludes that Bahtsul Masā'il serves not only as a forum for legal decision-making but also as an educational model for cultivating critical reasoning, collaborative scholarship, and methodological competence among pesantren scholars. These findings contribute to the development of Islamic legal studies and offer a conceptual framework for strengthening collective ijtihād in responding to contemporary challenges within Islamic educational institutions.